OPTIMALISASI PASCA PANEN KUNYIT DI UMKM SANS BERKAH EMPON - Sholihah, Efi Nikmatu; Nurhayati, Dewi Ratna; Cecilia, Fariska Della (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
Sans Berkah Empon is a business that handles various types of post-harvest empon, including turmeric. Sans Berkah Empon buys fresh turmeric from various locations in Central Java and East Java. The turmeric obtained is sold in various product forms, such as fresh turmeric that has been cleaned and sent to traditional markets and chopped turmeric that has been dried. Even though post-harvest processing has been carried out in the form of chopping and drying, most of the turmeric sold by Sans Berkah Empon is still fresh turmeric susceptible to rotting, mould and sprouting, so it requires proper treatment. The Community Service Team from the Faculty of Agriculture, Universitas Slamet Riyadi, provided training related to post-harvest optimization of empon-empon in July – September 2024 and based on the evaluation results there was an improvement in the quality of empon-empon and product diversification.